ANALISIS SIYASAH TANFIDZIYAH TERHADAP PENERAPAN PEDOMAN PENETAPAN DAN PENEGASAN BATAS DESA DI PROVINSI LAMPUNG - Fauzan Azhari; Fathul Mu'in; Nur Rahmah (CV Widina Media Utama, 2026)
This study aims to analyze the implementation of Minister of Home Affairs Regulation No. 45 of 2016 concerning Guidelines for the Determination and Delimitation of Village Boundaries in Lampung Province and to examine it from the perspective of Siyasah Tanfidziyah. Using a literature review (library research) with a legal and conceptual approach, the results of the study indicate that the delineation of village boundaries in Lampung Province is still hampered by conflicts between modern cartographic standards and claims to traditional boundaries, customary land rights, as well as the sectoral self-interest of village governments concerned about a reduction in village fund allocations. This uncertainty regarding territorial boundaries has a negative impact on the quality of civil registration services and risks triggering horizontal conflicts within agrarian communities. From the perspective of Siyasah Tanfidziyah, local governments, as ulil amri, are obligated to undertake proactive legal interventions to uphold the public interest (mashlahah mursalah) and mitigate harm (sadd adz-dzari’ah). However, for such regulations to possess strong moral and social legitimacy, policy implementation on the ground must integrate the principle of deliberation and accommodate the local wisdom (‘urf shahih) of indigenous communities. Therefore, this study recommends that the local government in Lampung Province expedite the issuance of the Regent’s Regulation through a participatory mediation approach that involves traditional leaders and village elders, in order to ensure orderly public administration and guarantee peace and tranquility in the lives of villagers ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi Peraturan Menteri Dalam Negeri Nomor 45 Tahun 2016 tentang Pedoman Penetapan dan Penegasan Batas Desa di Provinsi Lampung serta meninjaunya melalui perspektif Siyasah Tanfidziyah. Menggunakan metode penelitian kepustakaan (library research) dengan pendekatan perundang-undangan dan konseptual, hasil kajian menunjukkan bahwa penataan batas desa di Provinsi Lampung masih terhambat oleh benturan antara standar kartografis modern dengan klaim batas tradisional, hak ulayat, serta ego sektoral pemerintah desa yang khawatir akan penurunan alokasi dana desa. Ketidakpastian batas wilayah ini berdampak buruk pada penurunan mutu pelayanan administrasi kependudukan dan rentan memicu konflik horizontal di tengah masyarakat agraris. Dalam kacamata Siyasah Tanfidziyah, pemerintah daerah sebagai ulil amri berkewajiban melakukan intervensi hukum proaktif demi menegakkan kemaslahatan publik (mashlahah mursalah) dan memitigasi kerusakan (sadd adz-dzari’ah). Namun, agar regulasi tersebut memiliki legitimasi moral dan sosial yang kuat, eksekusi kebijakan di lapangan wajib mengintegrasikan asas musyawarah serta mengakomodasi kearifan lokal (‘urf shahih) masyarakat adat. Oleh karena itu, penelitian ini merekomendasikan pemerintah daerah di Provinsi Lampung untuk mempercepat penerbitan Peraturan Bupati melalui pendekatan mediasi partisipatif yang melibatkan para tokoh adat dan sesepuh kampung, guna mewujudkan tertib administrasi negara sekaligus menjamin ketenteraman kehidupan warga desa.